(untitled) (Research, Society and Development, 2020)
Objectives: analyze the needs of health guidelines for pregnant women on the pregnancy-puerperal cycle and discuss health education carried out by health professionals in prenatal care in the light of Paulo Freire. Methodology: descriptive research with a qualitative approach carried out from September to October 2019 with 27 pregnant women in a university hospital. Data were collected through semi-structured interview and later submitted to Bardin’s content analysis. Results: after the analysis, three categories emerged, namely: the needs for health guidelines of pregnant women about gestating, giving birth and postpartum; the popular knowledge of pregnant women about the pregnancy-puerperal cycle; and health education carried out by health professionals in prenatal care. In the analysis of the categories, it was noteworthy that health education carried out by health professionals didn’t fully address the real needs for health guidance presented by pregnant women. Conclusion: health education carried out by health professionals should not be imposed, and there should be a dialogical relationship that considers the sociocultural, psychological and biological aspects of pregnant women and their families and pre-existing knowledge in order to resignify them. This means is considered fundamental, so that based on pregnant women’s life contexts, there is greater possibility of obtaining the desired impact of health education, achievement of conscious and autonomous freedom of choice by pregnant women, health promotion, and self-care.